2014
DOI: 10.1002/anie.201404154
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Heparin‐Based Anticoagulant Drug Fondaparinux

Abstract: Fondaparinux, a synthetic pentasaccharide based on the heparin antithrombin-binding domain, is an approved clinical anticoagulant. Although it is a better and safer alternative to pharmaceutical heparins in many cases, its high cost, which results from the difficult and tedious synthesis, is a deterrent for its widespread use. The chemical synthesis of fondaparinux was achieved in an efficient and concise manner from commercially available D-glucosamine, diacetone α-D-glucose, and penta-O-acetyl-D-glucose. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 36 publications
1
42
0
2
Order By: Relevance
“…Through preparing various oligosaccharide fragments of FG, we found that compounds 5-7 may be desirable intrinsic tenase inhibitors because of their relatively low molecular weights, potent intrinsic anticoagulant activity, and negligible side effects. Notably, just as a pentasaccharide unit is the critical sequence within heparin chains required to bind and activate AT (40)(41)(42)(43), the nonasaccharide 5 is the minimum structural unit responsible for inhibiting human intrinsic tenase. The results of the antithrombotic assay show that compound 5 at 10 mg/kg has a similar antithrombotic effect as LMWH at 3.6 mg/kg.…”
Section: Compounds 5-8 Exhibit Strong Anticoagulant Activities By Selmentioning
confidence: 99%
“…Through preparing various oligosaccharide fragments of FG, we found that compounds 5-7 may be desirable intrinsic tenase inhibitors because of their relatively low molecular weights, potent intrinsic anticoagulant activity, and negligible side effects. Notably, just as a pentasaccharide unit is the critical sequence within heparin chains required to bind and activate AT (40)(41)(42)(43), the nonasaccharide 5 is the minimum structural unit responsible for inhibiting human intrinsic tenase. The results of the antithrombotic assay show that compound 5 at 10 mg/kg has a similar antithrombotic effect as LMWH at 3.6 mg/kg.…”
Section: Compounds 5-8 Exhibit Strong Anticoagulant Activities By Selmentioning
confidence: 99%
“…A pentaszacharid egy szintetikusan elõállított változatát 2001 óta alkalmazzák a gyógyászatban Arixtra ® (2) néven. [2][3][4] Az elmúlt másfél évtizedben a vegyület számos mimetikumát állították elõ, melyek elõdjüknél egyszerûbben és könnyebben szintetizálhatóak voltak. A vezérmolekula teljesen O-metilezett és O-szulfatált változata az idraparinux (3), 5,6 mely kiemelkedõ antikoaguláns aktivitással rendelkezik (1. ábra).…”
Section: Bevezetésunclassified
“…This has therapeutic implications and led to the development of a new generation of heparin derived anticoagulants including lowmolecular-weight heparins (LMWH) and fondaparinux. LMWH are obtained as fragments of unfractionated heparin as a result of enzymatic or chemical depolymerization, yielding to molecules of mean weight of 5000 Da (Table 1) 10 while fondaparinux is a synthetic pentasaccharide based on the heparin antithrombin-binding domain 11 . These medications target the anti-factor Xa activity rather than anti-thrombin (IIa) activity of AT-III, aiming to facilitate a more subtle regulation of coagulation with an improved therapeutic index and less side effects.…”
Section: The Physiological Role Of Heparinmentioning
confidence: 99%